Differential effects of modafinil, methamphetamine, and MDMA on agonistic behavior in male mice - Machalova, Alena; Slais, Karel; Vrskova, Dagmar; Sulcova, Alexandra (Pharmacology, biochemistry and behavior, 2012)
The aim of the present study was to compare the behavioral effects of modafinil, an atypical psychostimulatory acting and cognitive-function improving drug, with the effects of the psychostimulants methamphetamine (MET) and MDMA (3,4-methylenedioxymethamphetamine, or "ecstasy") in a model of mouse agonistic behavior. This model enables the observation of ethologically well-defined sociable, timid, aggressive, and locomotor behavioral acts and postures. Singly-housed male mice (isolates) were separated into 4 groups. The observations were performed in 4 sessions, 1 week apart. In each interaction, singly-housed mice were paired with non-aggressive group-housed partners for 4 min in a neutral environment. The isolates received, in a Latin square design, either a) a vehicle or modafinil at doses 2.0, 10.0, or 50.0 mg/kg; or b) a vehicle or MET at doses 1.0, 5.0, or 10.0 mg/kg; or c) a vehicle or MDMA at doses 2.5, 10.0, or 30.0 mg/kg. The isolates were categorized as timid or aggressive according to their behavior in the control interaction (vehicle pre-treatment). Elements of locomotor, sociable, aggressive, and timid behavior were evaluated (one-way ANOVA). In the aggressive mice, no change in the sum of aggressive behavior was measured following modafinil administration, while both methamphetamine and MDMA produced dose-dependent inhibition of aggression (p<0.01). The substantial difference in the tested drug effects on agonistic behavior was an increased occurrence of sociable acts (p<0.01) accompanied by a simultaneous increase of timid acts (p<0.01) recorded after MDMA, but not after modafinil or methamphetamine administration. In the timid mice, at least some doses of modafinil decreased timidity (p<0.01) and increased aggression (p<0.01) with no effect on sociability. Administration of MDMA increased timid activities (p<0.01). Both MDMA and MET decreased sociability (p<0.01).
Keywords: methamfetamin; N-Methyl-3,4-methylenedioxyamphetamine; Animals; vztah mezi dávkou a účinkem léčiva; Methamphetamine; benzhydrylové sloučeniny; chování zvířat; Mice; myši; agrese; Dose-Response Relationship, Drug; Benzhydryl Compounds; Male; N-methyl-3,4-methylendioxyamfetamin; Aggression; Behavior, Animal; stimulanty centrálního nervového systému; zvířata; mužské pohlaví; Central Nervous System Stimulants